Effects of liquid urea rates on nitrogen dynamics, growth, and yield of corn (Zea mays L.) - Md Motasim, Ahmmed; Samsuri, Abd. Wahid; Abdul Sukor, Arina Shairah; Akter, Amaily (Springer Nature, 2024)
Arbitrary use of urea fertilizer reduces nitrogen use efficiency (NUE) and increases the risk of environmental pollution. An experiment was conducted at the Universiti Putra Malaysia from November 2019 to March 2020 to evaluate the application methods and rates of liquid urea (LU) on the yield performance of corn. The treatments were, U0 = control, GU100 = Granular urea (GU) 100%, LU100 = LU 100%, LU50 = LU 50% and LU33 = LU 33%, in two equal splits at 10th and 28th days after sowing (DAS) in randomized completely block design, replicates four. Results showed that plant height (206.99 cm, 216.92 cm, 214.61 cm), ear height (88.13 cm, 88.63 cm, 86.00 cm), days of maturity (88.75, 89.00, 86.75 days), number of grains per kernel row (32.25, 34.50, 33.75), fresh cob weight (10,886.60 kg ha− 1, 10,946.60 kg ha− 1, 10,927.93 kg ha− 1) and 100-grain weight (20.51 g, 22.50 g, 21.39 g) of corn were not different significantly (p ≤ 0.05) in GU100, LU100 and LU50 treatments, respectively. The highest yield of corn was found with LU100 (6249.03 kg ha− 1) treatment whereas the yield in LU50 (5666.50 kg ha− 1) and GU100 (5746.64 kg ha− 1) were not different significantly. Nitrogen (%) in plants was the highest in LU100 followed by LU50 treatment which was significantly higher than GU100 treatment. The total N content was also the highest in LU100 (102.83 kg ha− 1) though the total N content was not different significantly in LU50 (77.62 kg ha− 1) and GU100 (83.84 kg ha− 1) treatments. The NUE was the highest in LU50 (66.92%) treatment followed by LU100 (51.47%) treatment. The results of the study suggested that LU was superior to GU and the LU100 was the best application rate while LU50 treatment was comparable to GU100 in corn cultivation.